CHANGES IN NITRIC OXIDE LEVELS AND ERYTHROCYTE ARGINASE ACTIVATES IN PATIENTS WITH DOWN SYNDROME - Ozbey, Ulku; Arslan, Cengiz; Seyran, Ayse; Erisir, Mine; Benzer, Fulya (John Wiley & Sons Inc, 2009)
[Abstract Not Available]